Age Estimation by Dental Eruption in Schoolchildren of 14-16 Years Age Group - Vijay Kumar AG1 , Suresh J2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The estimation of age is an important and is commonly carried in medico legal area. Assessment of age is often required while administering justice to an individual involved in the civil and the criminal litigation. Teeth are known to aid in personal identification and age estimation as they are highly durable and resist putrefaction, fire, chemicals etc. Objective: To study the status of dental eruption in schoolchildren of age group between 14- 16 years. The study was carried out involving 100 students of age group of 14-16 years from BGS High School, B G Nagara, Mandya District. Out of 100 subjects, 50 males and 50 females constituted the study population. In the present study, Upper jaw, on both right and left sides, there was no space behind 2nd molar tooth in 14 years males while space was present in one female of same age group. Only 1 male and 1 female of 15 years age group had developed space behind 2nd molar tooth. Considering the Lower jaw, space behind 2nd molar tooth was developed in 7 cases right side and 8 cases left side in case of 14 years boys. In case of girls of 14 years age it was present in 12 cases on right side and 9 cases on left side. In case of boys of 15 years, it was present in 18 cases on right side and 19 cases on left side. In case of girls of 15 years, it was present in 18 cases on right side and 20 cases on left side. The dental system is an integral part of the human body, its growth and development can be studied in parallel with other physiological maturity indicators such as bone age, menarche and height.